2022
DOI: 10.1017/s0029665122002786
|View full text |Cite
|
Sign up to set email alerts
|

Impact of obesity and diet on brain structure and function: a gut–brain–body crosstalk

Abstract: Most societies witness an ever increasing prevalence of both obesity and dementia, a scenario related to often underestimated individual and public health burden. Overnutrition and weight gain have been linked with abnormal functionality of homoeostasis brain networks and changes in higher cognitive functions such as reward evaluation, executive functions and learning and memory. In parallel, evidence has accumulated that modifiable factors such as obesity and diet impact the gut–brain axis and modulate brain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 94 publications
0
6
0
Order By: Relevance
“…According to studies by Medawar et al, 2022, people who have a higher BMI and more visceral fat also tend to have more subtle grey matter atrophy and white matter lesions, a different hypothalamic microstructure, and decreased thickness, memory, and connectivity in reward and default mode network regions. Analysis of mediation showed that localized anomalies linked to obesity result in cognitive deficits and that increasing visceral fat adversely affects brain tissue via systemic low-grade inflammation [ 19 ]. Similarly, memory and neuroanatomical assessments were shown to be generally declining in our study.…”
Section: Discussionmentioning
confidence: 99%
“…According to studies by Medawar et al, 2022, people who have a higher BMI and more visceral fat also tend to have more subtle grey matter atrophy and white matter lesions, a different hypothalamic microstructure, and decreased thickness, memory, and connectivity in reward and default mode network regions. Analysis of mediation showed that localized anomalies linked to obesity result in cognitive deficits and that increasing visceral fat adversely affects brain tissue via systemic low-grade inflammation [ 19 ]. Similarly, memory and neuroanatomical assessments were shown to be generally declining in our study.…”
Section: Discussionmentioning
confidence: 99%
“…External factors also have a big influence because from an early age the environment judges fat people as lazy, stupid and slow. (Medawar & Witte, 2022)…”
Section: Psychosocial Impactmentioning
confidence: 99%
“…Diet and obesity can blunt higher cognitive (hippocampal and PFC) functioning, which negatively influences future decision making in support of health behaviors. Investigations in mouse models have not revealed conclusive mechanisms, whereby obesity and undernutrition affect neuronal circuitry [94,95]. Although current technologies have revealed the architecture of neuronal connections and synapses in mice, they cannot detect changes in the strength of existing brain connections at synaptic and axonal development levels.…”
Section: The Effects Of Adiposity On the Competing Homeostatic And He...mentioning
confidence: 99%